The Impact of Air Resistance on the Fuel Consumption in Real Conditions within the Transport Operation - Rievaj, Vladimir; Stopka, Ondrej; Vrabel, Jan; Mokrickova, Lenka; Schmidt, Conrad (Communications - Scientific letters of the University of Zilina, 2016)
This paper presents the impact of air resistance (air resistance) on fuel consumption of the particular vehicle under real traffic conditions. In the introductory and subsequent part of the paper, the individual resistances influencing the moving vehicle are characterized. In the following chapter, the specific factors such as air resistance, driving speed, air temperature and air resistance coefficient in the context of their impact on fuel consumption of the particular vehicle are identified and described; as well as the comparisons of fuel consumption when the vehicle is moving on the highway with closed and open windows under different conditions of road traffic are performed.